(3HjY GdeRGjOI aj Gdabg GdESdGej (B/s - (3bGSe Ydj, eMeO Ydjs ((3GdGScfOQjI(B: s (3OGQ GdLGeYI GdLOjOI ddfTQ hGdJhRjY(B, s, 2002)
(3JYQja HjY GdeRGjOI hGbSGeg heTQhYg(B- (3JYQja HjY GdeRGjOI ,eTQhYjI HjY GdeRGjOI hNUGFUg,UhQI ef GdHjhY GdJj JeGQS HGdeRGjOI (B- (3GMcGe GdeRGjOI , GdGjLGH hGdbHhd aj HjY GdeRGjOI , VhGHWg , GdGMcGe GdfJYdbI HGdOdGds
Keywords: (3Gdabg GdGSdGejs; (3GdeRGO GdYdfjs; (3GdeRGjOIs